Definition of species of pouched four-eyed opossums (Didelphidae, Philander) - Patton, James L.; Silva, Maria Nazareth Ferreira da (Journal of Mammalogy, 1997)
We hypothesize phyletic relationships among taxa of the didelphid marsupial genus Philander, based on sequences of the mitochondrial cytochrome b gene. Data are available for six taxa recognized at either the specific or subspecific levels; P. opossum opossum Linneaus (eastern and northeastern Amazonia), P. opossum canus Osgood (western Amazonia), P. opossum fuscogriseus J. A. Allen (southeastern Central America), P. opossum frenata Olfers (southeastern Brazil), P. andersoni andersoni Osgood (northwestern Amazonia), and P. andersoni mcilhennyi Gardner and Patton (west-central Amazonia). Haplotype divergence is minimal to non-existent (<1% on average) between individuals within and among localities for each taxon. The taxon inhabiting the Atlantic forest of coastal Brazil (P. o. frenata) is highly divergent from all others, averaging nearly 14% in sequence divergence. Maximal divergence among haplotypes representative of the other taxa examined is <8%. The combination of phylogenetic relationships and local sympatry suggests a greater degree of species diversity for the genus than the two species P. opossum and P. andersoni. We recognize the Brazilian coastal P. frenata, as well as both P. andersoni and P. mcilhennyi, as valid species in addition to P. opossum. It is possible P. opossum is a composite, and that further studies will accord species status to the Middle American, western Amazonian, and eastern Amazonian-Guianan gray four-eyed opossums.
Keywords: Didelphidae; Metatheria; Philander; Philander Andersoni; Philander Frenata; Philander Mcilhennyi; Philander Opossum